Room Temperature Electrodeposition of Ready-to-Use TiOx for Uniform p-n Heterojunction Over Nanoarchitecture - Cao, Yufeng; Qiao, Huajian; Zou, Yalong; An, Na; Zhou, Yang; Liu, Deyu; Kuang, Yongbo (Frontiers in Chemistry, 2022)
The photocathodes are essential in photoelectrochemical systems for harvesting solar energy as green fuels. However, the light-absorbing p-type semiconductor in them usually suffers from carrier recombination issues. An effective strategy to address it is fabricating the p-n heterojunction to create an interfacial electric field. However, plenty of deposition process of the n-type layer for this purpose requires either sophisticated instruments or subsequent treatments, which may damage the vulnerable p-type structure. Herein, we report a mild approach for a ready-to-use n-type layer with full functionality. Structural analyses proved the successful coating of a uniform titania layer (up to 40 nm) over Cu2O without damaging its structure. Owing to the high Ti3+ content, the layer possesses excellent charge transport ability and requires no additional annealing. The heterojunction effectively facilitates the carrier separation and positively shifts the photocurrent onset potential for 0.2 V. The Mott–Schottky plot and the impedance study reveal an enhanced carrier collection with reduced charge transfer resistances. Such a nano-heterojunction can be further loaded with the hydrogen evolution catalyst, which almost doubles the photocurrent with an extended lifetime than that of the pristine Cu2O nanoarray. This approach puts forward a potentially scalable and efficient choice for fabricating photoelectrochemical devices.